Die pluralisme van wêreldbeskouinge, teoretiese paradigmas en teorieë - Botha, M. Elaine (Koers, 1984)
The actual existence of a large variety of schools, trends, viewpoints and theories in practically every science confronts the Christian scholar with a difficult choice. The question facing the Christian scholar is whether, in the face of this plethora of theories, he has to work out theories de novo. This immediately implies a question of criteria.